The Numerical Simulations of Clay-Concrete Interface Tests on the Mesoscopic Level - Yang Jinwen; Zhao Jianming; Liu Xiaosheng (MATEC Web of Conferences, 2018)
The issue of the interface between soils and structures is an important research area in the high embankment dam. The particle flow code (PFC3D) that uses the discrete element method, can be used to research various geotechnical engineering problems, including the interface problems. Numerical simulations by PFC3D entail the mesoscopic parameters of walls and particles, i.e. the cohesion strength, tensile strength, the wall friction and the interparticle friction that are critical to determine whether the results of the simulations can be consistent with those of tests. On the basis of a large number of numerical simulation tests, this paper tries to reveal the connections between these mesoscopic parameters and macroscopic mechanical properties in the clay-concrete interface tests. Then macroscopic and mesoscopic properties of the interface are analysed by numerical simulations.